Pendampingan Community Based Surveilance Sebagai Upaya Pengendalian Tuberkulosis Paru di Kelurahan Bandengan - Nonik Eka Martyastuti; Jaya Maulana (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Tuberculosis (TB) is an infection caused by Mycobacterium tuberculosis. Indonesia is among the three countries with the highest estimated incidence of TB, after India and China. Tuberculosis deaths in HIV-negative populations reach 44 per 100,000 population (WHO, 2019). Bandengan village now has 8 cases, the second highest in the Doukh Health Center's service area. In addition to the high number of new cases, public participation in programs to combat and prevent pulmonary tuberculosis is also low. Many philanthropic efforts have been put into place to help solve this problem, including Trained and formed community-based health worker monitoring teams and educated in early detection and prevention of pulmonary tuberculosis. Indicators of success for this community service included increasing residents' knowledge, skills, and independence in community-based monitoring programs, forming community-based monitoring teams in villages, and increasing community awareness and role in pulmonary tuberculosis prevention. will be the activity was held on Tuesday 24th January 2023 with her 20 participants. Partners play a central role in this activity as this service is a community empowerment activity and partners are the main actors/actors. The proposal team will act as a facilitator and companion until the partners are deemed competent and independent to continue community-based surveillance (CBS) activities to combat pulmonary tuberculosis in Bandengan village.